Pengaruh Model Komunikasi Terapeutik dan Kompetensi Tenaga Kesehatan Terhadap Kenyamanan Pasien di Klinik Pratama St. Martin De Porres Ende - Agueda Da Conceicao; Dasrun Hidayat; Yani Restiani Widjaja (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
This study aims to analyze the influence of therapeutic communication and health worker competence on patient comfort at the St. Martin de Porres Primary Clinic. Patient comfort is seen as an indicator of the quality of primary health care services that include physical, emotional, social, and psychological dimensions. Method The type of mixed method research used in this study is the Explanatory Sequential Design, starting with quantitative research used through a survey of 100 respondents with complementary qualitative data from interviews with eight informants. The results of the partial regression test showed that therapeutic communication had a significant effect on patient comfort, while health worker competence did not show a significant effect. However, simultaneously both variables had a significant effect with a contribution of 9%. Qualitative findings support the importance of empathetic communication and professionalism in creating comfort. This study recommends the development of more valid instruments and exploration of intermediary variables such as trust and perception of facilities, with a mixed-method approach or Structural Equation Modeling (SEM) for more comprehensive analysis in the future.